Top secret training data? External training loads of a cup winning English Super League rugby league team - Black, C. J.; Till, K.; O`Hara, J. P.; Davidson, J.; Jones, B. (International Journal of Sports Science & Coaching, 2018)
This study quantified the field-based external training loads of professional rugby league players using global positioning systems technology across a playing season. Eleven professional rugby league players were monitored during all field-based training activities during the 2014 Super League season. Training sessions undertaken in preseason (n=211 observations), early (n=194 observations), middle (n=171 observations) and late (n=206 observations) phases of the in-season were averaged for each player and used in the analyses. Large reductions in external training loads between preseason and in-season periods were observed. Within season, a decrease in intensity (relative distance, absolute and relative total-HSR) with a limited change in training duration was observed. These data provide a useful reference for coaches working with similar cohorts, while future research should quantify the adequacy of the training loads reported, considering impact on performance and injury. ABSTRACT FROM AUTHOR